2003
DOI: 10.1155/2003/716490
|View full text |Cite
|
Sign up to set email alerts
|

Waiting-List Induced Proctitis: The Hydrogen Peroxide Enema

Abstract: Hydrogen peroxide is a widely available disinfectant that has been reported to cause colitis. We report a case of a 67-year-old man who presented with an acute proctitis caused by a self-inflicted 3% hydrogen peroxide enema. The patient's intention was to cure himself of a recently diagnosed prostate cancer, because the waiting list for oncological consultation was deemed too long. The pathogenesis of hydrogen peroxide mucosal injury and a review of the literature is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Like other injury, the pathogenesis of hydrogen peroxide colitis is thought to be secondary to the chemical reaction resulting in penetration of highly reactive oxygen species, resulting in damage to the colonic mucosa [6,7]. The volume of oxygen liberated from the decomposition of hydrogen peroxide can be considerable, with 30 mL of 35% hydrogen peroxide yielding 3.5 L of oxygen, and it is thought to be secondary to absorption of hydrogen peroxide into the epithelial interstices and capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…Like other injury, the pathogenesis of hydrogen peroxide colitis is thought to be secondary to the chemical reaction resulting in penetration of highly reactive oxygen species, resulting in damage to the colonic mucosa [6,7]. The volume of oxygen liberated from the decomposition of hydrogen peroxide can be considerable, with 30 mL of 35% hydrogen peroxide yielding 3.5 L of oxygen, and it is thought to be secondary to absorption of hydrogen peroxide into the epithelial interstices and capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Bassan et al 13) reported a near-fatal air embolism after the use of hydrogen peroxide solution to wash the enclosed body parts. In some previous studies, most patients exposed to 3% hydrogen peroxide showed mild gastrointestinal symptoms, but developed hematochezia, lower abdominal pain, and tenesmus, and then recovered from a transient injury 14,15) .…”
Section: Pediatric Emergency Medicine Journalmentioning
confidence: 89%
“…It may be effective since patients tend to follow the advice of a competent physician over information obtained from the Internet [ 18 ]. Hydrogen peroxide has also been used for other indications like enlarged prostate and cancer of prostate [ 7 ]. Therefore, patients with unexplained colitis or proctitis may be queried about use of hydrogen peroxide enema.…”
Section: Discussionmentioning
confidence: 99%